Dynamics of Short Recoil-Operated Weapon - Martin MACKO (Wojskowa Akademia Techniczna, 2021)
In this article, the authors mentioned the function of short-recoil-operated weapons with a vertical sliding-wedge breechblock. The dynamic simulation was conducted and then the results were compared with the corresponding experimental data to verify reliability of the model. The model is calculated and tested out on the 37 mm twin anti-aircraft gun. Besides, the article presents the effect of some structural parameters on functionality of the automatic weapon. The reported results are an important theoretical basis to determine the rate of fire and the forces acting on the guns. The movement of the breechblock also affects stability of the weapon and can therefore be used to a math model or to simulate the movement of the weapon. Calculated and verified data could be used for the design of an automatic firing system as well as for solving vibration on automatic guns when burst firing.
Keywords: Badania broni strzeleckiej